A Multicenter Evaluation of Off-Label Medication Use and Associated Adverse Drug Reactions in Adult Medical ICUs. Issue 8 (August 2015) - Smithburger, Pamela L.; Buckley, Mitchell S.; Culver, Mark A.; Sokol, Sarah; Lat, Ishaq; Handler, Steven M.; Kirisci, Levent; Kane-Gill, Sandra L.
Abstract : Objective: Prior research indicates that off-label use is common in the ICU; however, the safety of off-label use has not been assessed. The study objective was to determine the prevalence of adverse drug reactions associated with off-label use and evaluate off-label use as a risk factor for the development of adverse drug reactions in an adult ICU population. Design: Multicenter, observational study Setting: Medical ICUs at three academic medical centers. Patients: Adult patients (age ≥ 18 yr old) receiving medication therapy. Interventions: All administered medications were evaluated for Food and Drug Administration–approved or off-label use. Patients were assessed daily for the development of an adverse drug reaction through active surveillance. Three adverse drug reaction assessment instruments were used to determine the probability of an adverse drug reaction resulting from drug therapy. Severity and harm of the adverse drug reaction were also assessed. Cox proportional hazard regression was used to identify a set of covariates that influenced the rate of adverse drug reactions. Measurements and Main Results: Overall, 1, 654 patient-days (327 patients) and 16, 391 medications were evaluated, with 43% of medications being used off-label. One hundred and sixteen adverse drug reactions were categorized dichotomously (Food and Drug Administration or off-label), with 56% and 44% being associated with Food and Drug Administration–approved and off-label use, respectively. The number of adverse drug reactions for medications administered and the number of harmful and severe adverse drug reactions did not differ for medications used for Food and Drug Administration–approved or off-label use (0.74% vs 0.67%; p = 0.336; 33 vs 31 events, p = 0.567; 24 vs 24 events, p = 0.276). Age, sex, number of high-risk medications, number of off-label medications, and severity of illness score were included in the Cox proportional hazard regression. It was found that the rate of adverse drug reactions increases by 8% for every one additional off-label medication (hazard ratio = 1.08; 95% CI, 1.018–1.154). Conclusion: Although adverse drug reactions do not occur more frequently with off-label use, adverse drug reaction risk increases with each additional off-label medication used. Abstract : Supplemental Digital Content is available in the text.